2016
DOI: 10.4103/1817-1745.181249
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal endoscopic repair of pediatric meningoencephalocele

Abstract: Introduction:Encephaloceles in relation to the nose are rare lesions affecting the skull base. In the pediatric population, majority are congenital lesions manifesting as nasal masses requiring surgical intervention.Materials and Methods:A retrospective study of 6 consecutive patients below 12 years of age with intranasal meningoencephalocele treated by endonasal endoscopic approach at our tertiary centre was done. The follow up period ranged from 6 months to 2 years. A detailed clinical and radiological evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 8 publications
1
16
0
1
Order By: Relevance
“…Pure endoscopic repair of anterior skull base defects in children has been previously described 23 ; however, with such large bony defects as seen in our cases, a purely endoscopic approach in children this young would be difficult, particularly in the case of the nasofrontal encephalocele (case 2). Additionally, small nares in babies in the first days of life create technical challenges regarding purely endoscopic repair.…”
Section: Discussionmentioning
confidence: 74%
“…Pure endoscopic repair of anterior skull base defects in children has been previously described 23 ; however, with such large bony defects as seen in our cases, a purely endoscopic approach in children this young would be difficult, particularly in the case of the nasofrontal encephalocele (case 2). Additionally, small nares in babies in the first days of life create technical challenges regarding purely endoscopic repair.…”
Section: Discussionmentioning
confidence: 74%
“…This pathology is described as an encephalocele when the sac contains neural elements and as a meningocele when no recognizable brain tissue is present within the sac. 34,35 Patients with a history of rhinorrhea or meningitis were selected for surgery. Before surgery, CT was performed to determine the bony defect and MRI was conducted to identify the contents and size of the meningocele.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic repair of the meningocele defect is a minimally invasive procedure and is advised for successful treatment of the lesions. [34][35][36] Keshri et al reported six patients with meningocele who underwent surgery using the transnasal endoscopic approach. 35 Ma et al reported a series of 23 patients who underwent surgery for CSF leak with or without encephalocele, 28 and Marfatia et al reported a series of 19 pediatric patients with meningoencephaloceles who underwent surgery.…”
Section: Discussionmentioning
confidence: 99%
“…EES avoids the additional morbidity of open approaches and is effective in long-term follow-up. 13,27 The goals of surgery are to resect the encephalocele, minimize any injury to normal brain tissue and vessels, and provide a watertight seal to divide the sinonasal and intracranial contents.…”
Section: Encephalocelementioning
confidence: 99%